Faktor-Faktor yang mempengaruhi Keputusan Pembelian Melalui Moderasi Brand Image (Studi Kasus pada Calon Mahasiswa Baru Institut Pariwisata Trisakti Dalam Memilih Kampus) - Sembiring, Vienna Artina; Sugeng, Novita Widyastuti; Ratu Bilqis, Linda Desafitri; Sabda, Christophorus (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
Competition between educational institutions, especially at the tertiary level, is getting tighter in line with the rapid development of the world of education today. Each university tries to highlight its advantages in order to attract potential students to choose their institution. The purchasing decision is a crucial step for prospective students in choosing the right educational institution. This research aims to identify the influence of customer perception, visiting experience, and brand image on purchasing decisions of prospective new students at higher education institutions. Using a quantitative approach, this research collected data from 100 student respondents from the class of 2024 at the Trisakti Tourism Institute through a questionnaire. The results of the analysis show that positive perceptions and good visiting experiences significantly influence purchasing decisions, with brand image as a moderating factor that strengthens this relationship. Keywords: Purchase Decision; Customer Perception; Visiting Experience; Brand Image.